Interrelationships among mineral levels in soil, forage, and animal tissues on ranches in northern Mato Grosso. I. Calcium and phosphorus - Sousa, J. C. de; Conrad, J. H.; Blue, W. G.; Mcdowell, L. R. (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted with samples from six farms in northern Mato Grosso, Brazil, to study the interrelationships between level of minerals in soil, forage, and animal tissues during the wet and dry seasons of the year. Soil extractable Ca, forage Ca, and rib bone ash Ca were normal during both seasons. Soil extractable P ranged from 2.5 to 27.6 ppm which is considered low to average. Forage P was deficient for grazing cattle and ranged from 0.07 to 0.18%. Rib bone ash phosphorus levels ranged from 15.1 to 15.5% and they are considered borderline to deficient. Mean rib bone ash P during the dry season was greater than during the wet season, even when forage phosphorus levels were lower. This indicates a higher requirement during the wet compared with the dry season. Rib bone ash P was positively correlated with soil Ca, forage Ca, rib bane ash Ca, and soil P.